Analiza wpływu wybranych czynników na popyt na usługę zarządzania funduszem inwestycyjnym - Łukojć, Adam; Białomazur, Iwona (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The authors try to identify the main factors impacting the value of inflows to mutual funds in Poland. The inflows to mutual funds are compared to the following data: costs (total expense ratios), investment performance in the current and previous year, and fund size. The data was collected from 451 financial statements of Polish mutual funds, for the years 2012–2016. The funds belong to three categories: bond, equity, small, and mid cap equity. The findings suggest that the connection between the funds fees — the price — and inflows to funds is relatively weak. Investment performance in the same year is the only factor that shows significant correlation with mutual fund flows
Keywords: fundusze inwestycyjne; decyzja inwestycyjna; zarządzanie; opłaty